Relasi Makna dalam Lirik Lagu Perjuangan Nahdlatul Wathan Karya TGKH. M. Zainuddin Abdul Majid (Kajian Semantik) - Wijaya, Herman; Wartini, Laila Sufi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This study aimed to describe the semantic relation of words in the lyrics of Struggle song of Nahdlatul Wathan worked TGKH. M. Zainuddin Abdul Majid with semantic study. The method used in this research is descriptive method with a form of qualitative research. The data in this study are the words that contain the semantic relationships in lyrics of Struggle song of Nahdlatul Wathan worked TGKH. M. Zainuddin Abdul Majid with semantic study. Sources of data in this study is the lyrics of Struggle song of Nahdlatul Wathan created by TGKH. M. Zainuddin Abdul Majid. Technique used in this research is interview and documentary studies. Data analysis technique is done through a phase of data reduction, data presentation, and concluded the data. Based on the results of data analysis, it can be deduced that the lyrics of Struggle song of Nahdlatul Wathan worked TGKH. M. Zainuddin Abdul-Majid are synonyms, antonyms, homonyms, hyponymy and hypernymy, redundancies and polysemy. Every relationship has a meaning that can be a lesson in social life. The songs contained on the teachings and exhortations, that as Muslims must maintain, strengthen faith and piety to Allah. In addition, as a citizen of Nahdlatul Wathan should be invited to foster a spirit of faith and devotion as a support to form the spirit of diversity and nationality.Keywords: Meaning Relationship; Semantic Study; Struggle Song.